Tremella fuciformis polysaccharides alleviate induced atopic dermatitis in mice by regulating immune response and gut microbiota - Xie, Lingna; Yang, Kaiye; Liang, Yiheng; Zhu, Zhenyuan; Yuan, Zhengqiang; Du, Zhiyun (Frontiers in Pharmacology, 2022)
Atopic dermatitis (AD), characterized by severe pruritus, immune imbalance, and skin barrier dysfunction, has a high incidence worldwide. Recent evidence has shown that the modulation of gut microbiota is crucial for alleviating clinical symptoms of AD. Tremella fuciformis polysaccharides (TFPS) have been demonstrated to have a variety of biological activities such as immunomodulatory, anti-tumor, antioxidant, anti-inflammatory, neuroprotective, hypoglycemic and hypolipidemic effects. However, their effects on AD treatment have never been investigated. In this study, we compared the therapeutic effects of topical or oral administration of TFPS on AD in dinitrofluorobenzene (DNFB)-induced AD mice. Both topical application and oral administration of TFPS led to improvement on transdermal water loss, epidermal thickening, and ear edema in AD mice, but the oral administration showed significantly better efficacy than the topical application. The TFPS treatment increased the proportion of CD4(+) CD25(+) Foxp3 (+) regulatory T cells in mesenteric lymph nodes. Additionally, the non-targeted metabolomics and sequencing of 16S rDNA amplicons were performed, revealing metabolite modulation in feces and changed composition of gut microbiota in mice, which were induced for AD-like disorder and treated by oral administration of TFPS. Collectively these data suggest that the oral administration of TFPS may constitute a novel effective therapy for AD, with underlying mechanisms associated with the regulation of immune response, and improvement of both metabolism and the composition of intestinal microbiota.